Synthesis of pentaerythritol stearate ester-based zinc alkoxide and its synergistic effect with calcium stearate and zinc stearate on PVC thermal stability - Liu, H.; Li, D.; Li, R.; Sun, Hongqi; Zhang, Y.; Zhang, L.; Zhao, P. (2018)
A novel pentaerythritol stearate ester-based zinc alkoxide (PSE-Zn) was synthesized through a two-step method. Zinc ethoxide was first prepared from zinc acetate and ethanol, and then with ethanol as the solvent, the obtained zinc ethoxide ester was heated together with pentaerythritol stearate to produce PSE-Zn. PSE-Zn could be used as a promising poly(vinyl chloride) (PVC) thermal stabilizer. Conductivity tests, thermal aging tests, and UV-visible spectroscopy were used to study the thermal stabilization performance of the thermal stabilizers of PSE-Zn on PVC. The results showed that, with a lower melting point and a good compatibility with PVC, PSE-Zn presented a significant improvement in maintaining the initial color of PVC. However, the color of PVC stabilized with pure PSE-Zn began to degrade when the sample was heated at 180°C for 60 min indicating the unsatisfactory long-term thermal stability presented by PSE-Zn on PVC. So, some commercial thermal stabilizers, for example, calcium stearate (CaSt 2 ), zinc stearate (ZnSt 2 ), or CaSt 2 /ZnSt 2 were employed along with PSE-Zn to further improve the stabilizing performance. The results showed that there was a synergistic effect that was between 2 phr PSE-Zn and 2 phr CaSt 2 and made the stabilized PVC possess the best thermal stability. Because of the presence of free hydroxyl in PSE-Zn, which could chelate ZnCl 2 , PSE-Zn can then restrain "zinc-burning" phenomenon when PSE-Zn and ZnSt 2 were used together. It was also found that PVC stabilized with 3 phr PSE-Zn and 1 phr CaSt 2 /ZnSt 2 had the best color stability. The mechanism of thermal stability of PSE-Zn was also discussed. As a metal alkoxide, PSE-Zn is readily to neutralize HCl. In addition, PSE-Zn is able to replace the allyl chloride to terminate the dehydrochlorination of PVC. Moreover, because of the stearate radicals, PSE-Zn had a very low melting point, a better compatibility with PVC, and a lubrication action. With these excellent properties, PSE-Zn would be able to make PVC achieve an excellent initial color and a long-term stability.